(untitled) (Research, Society and Development, 2022)
Healthcare-related infections are a worldwide concern, as they increase morbidity and mortality of hospitalized patients, especially those in intensive care units. When the etiology of these infections is a multidrug-resistant microorganism, complications in treatment are even greater, and there are limited options for management. Thus, this study analyzed the occurrence of such infections in the intensive care units of the Campos Gerais Regional University Hospital from January 2017 to December 2019 by analyzing the spreadsheets provided by the Center for Hospital Infection Control and subsequent analysis of prevalence, means and medians by Excel software with the aim of profiling the patients most susceptible to contracting these infections and to analyze the microbiological profile of the sample. As for the epidemiological profile, most cases were registered in men, people over 60 years old, and patients with comorbidities. As for the microbiological profile found, the most prevalent bacteria was Klebsiella pneumoniae, with 34 cases, followed by Staphylococcus aureus, responsible for 33 occurrences. The most frequently observed resistance mechanism was methicillin-resistant Staphylococcus aureus. We conclude that infections caused by multidrug-resistant microorganisms are a concern for professionals who work in hospitals, especially in intensive care units, and that they should pay attention to preventive measures and conscientious use of antimicrobials.